Distribution of GSTM1 and GSTT1 polymorphisms among caucasians and the three major ethnic groups in Malaysia - Wan Rashidi, Wan Nooremira (2018)
Glutathione S-transferases (GSTs) are the vital Phase II enzymes to detoxify carcinogens and reactive oxygen species in the body, which encoded by GST mu class 1 (GSTM1) and GST theta class 1 (GSTT1) genes. Polymorphism in the genes affects the enzyme expression and increases the susceptibility to disease. GSTM1 and GSTT1 deletions present in 50% and 20% of Caucasian population, 54% and 37% in Africans, and 62% and 20% in Asians, respectively, showing ethnicdependent polymorphism of both genes. However, the genetic polymorphisms are less reported in Malaysia predominantly between three major ethnics; Malay, Indian and Chinese. In addition, the rate of GST polymorphisms in Malaysia has not been precisely compared with Caucasian population using the standard genome reference, European Collection of Cell Culture (ECACC). Therefore, this research was to determine the distribution of GSTM1 and GSTT1 polymorphisms among three different ethnic groups in Malaysia and Caucasians. One to three milliliters of peripheral blood were collected from 518 individuals comprised of 262 Malays, 151 Chinese and 105 Indians. DNA was extracted using QIAamp DNA blood mini kit and quantified using NanoDrop™ Lite Spectrophotometry. Meanwhile, 192 DNA samples (ECACC HRC-1 and HRC-2) were commercially bought to represent Caucasians group. All DNA samples proceed with multiplex PCR to determine GSTM1 and GSTT1 deletion simultaneously in the presence of internal control, Albumin (ALB) gene. The genotypes were then validated using DNA sequencing. Chi Square test was carried out to compare the genotype frequencies among three Malaysian ethnic groups and between the whole study cohort in Malaysia and Caucasians at p<0.05 as significant difference level. This study recorded three categories of genotypes; GSTM1 null, GSTT1 null, and combined GSTM1 and GSTT1 null. There was a significant difference between the three Malaysian ethnic groups in all genotype categories (p<0.001). GSTM1 null was found in 62.2% of Malays, 48.3% of Chinese and 29.5% of Indians. As for GSTT1, the null frequency was higher among Chinese (47.7%) followed by Malays (39.7%), and lowest in Indians (9.5%) respondents. Meanwhile, the combined null genotypes were recorded in 26.0% of Malay, 21.2% of Chinese, and 2.9% of Indian. In overall, the whole study cohort in Malaysia and Caucasians were significantly different in the null genotype of GSTT1 and combined genes (p<0.001). Malaysia has a higher null frequency of 35.9% for GSTT1 and 19.9% for combined genes than Caucasians (16.7% for GSTT1 and 8.9% for combined genes). The distributions of GSTM1 in Malaysia are similar to those reported among Africans, Caucasians and Asians whereas the frequency of GSTT1 null varies among those populations. In conclusion, Malaysia has a high rate of GSTM1 and GSTT1 null genotypes, and Malays showed the highest frequency among the three major ethnics. This study provides further evidence for ethnic variation in metabolism and disposition, and these genotype data will help future genetic studies on the GST polymorphisms in association with disease risks and drug effects in Malaysia.